FEMINIST THERAPY ISLAM SEBAGAI ALTERNATIF MENANGANI KORBAN KEKERASAN DALAM RUMAH TANGGA - Ade Nurzaman (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2017)
Abstract. Figures Domestic Violence (domestic violence) both in quantity and quality tends to increase, this could be caused by several things. First, public awareness of human rights has become part of people's lives. Second, because many institutions are quite concerned with the phenomenon of domestic violence so that they can report the numbers of the violence. During the handling of domestic violence is still limited to the victims of violence. Approach to counseling theories that are considered relevant to the case of domestic violence is feminist therapy Islam (Islamic feminist therapy). The concept is built on feminist theory wear integrated systems perspective with Islamic psychology, counseling intervention process means not only to individuals but individuals join the neighborhood to be treated to ensure the completion of the root of the problem is even a touch of spiritual and religious. Counselor ability to empower individuals / communities in the victim a skill that must be honed by a counselor who wears feminist therapy. This theory is based on the principle, namely; First, the personal is political; Second, egalitarian relationships, and third, the valuing perspective. The third concept of the pillars of feminist therapy and weighed with religion becomes an important indicator in determining the ability of the counselor to help assist victims of domestic violence.